1985
DOI: 10.1128/aem.49.1.132-136.1985
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal distribution of Vibrio parahaemolyticus in freshwater environs and in association with freshwater fishes in Calcutta

Abstract: The seasonal distribution of Vibrio parahaemolyticus in freshwater environs and in association with freshwater fishes was studied in 1982 and 1983. The occurrence of this organism in water and sediments at the three sites studied was very infrequent and was restricted to the summer months, although it was not always isolated during these months. The association of V. parahaemolyticus with plankton was chiefly confined to the summer months and progressively declined with the onset of monsoons, remaining below d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 10 publications
1
23
1
1
Order By: Relevance
“…An abundance of V. parahaemolyticus was seen in the water compared to plankton. This was in contrast to other studies where higher densities of V. parahaemolyticus were obtained from plankton [26,27]. However, higher numbers of the bacterium were found in the Georgian coastal waters [28].…”
Section: Discussioncontrasting
confidence: 95%
“…An abundance of V. parahaemolyticus was seen in the water compared to plankton. This was in contrast to other studies where higher densities of V. parahaemolyticus were obtained from plankton [26,27]. However, higher numbers of the bacterium were found in the Georgian coastal waters [28].…”
Section: Discussioncontrasting
confidence: 95%
“…Several workers have identified the organism in European coastal waters (Hechelmann et al 1971 (Heinemeyer 1984). The occurrence of these halophilic organisms in freshwater environments, however, is exceptional and it has hitherto been reported from only Calcutta (Sarkar et al 1983(Sarkar et al , 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of other workers have shown that water and sediments offer a rather limited ecological niche for V . parahuemolyticus (Kaneko & Colwell 1973;Sarkar et a/. 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Green fluorescent protein (GFP) tracing has been utilized to indirectly locate V. parahaemolyticus in the gills and other tissues (Cabello et al 2005). Although V. parahaemolyticus has been detected in the gills (Sarkar et al 1985;Cabello et al 2005;Luan et al 2008) and in individual oysters (Parveen et al 2008), the actual levels of the pathogen in specific oyster tissues are not yet clear. Therefore, this study investigated the abundance of V. parahaemolyticus (ATCC 17802) in various oyster tissues following artificial contamination and depuration, to determine which tissues may be suitable for direct monitoring of this pathogen.…”
Section: Introductionmentioning
confidence: 99%